Defining the role of Porphyromonas gingivalis peptidylarginine deiminase (PPAD) in rheumatoid arthritis through the study of PPAD biology. Issue 11 (26th May 2014) - Konig, Maximilian F; Paracha, Alizay S; Moni, Malini; Bingham, Clifton O; Andrade, Felipe
Abstract : Background: Antibodies to citrullinated proteins are a hallmark of rheumatoid arthritis (RA). Porphyromonas gingivalis peptidylarginine deiminase (PPAD) has been implicated in the initiation of RA by generating citrullinated neoantigens and due to its ability to autocitrullinate. Objectives: To define the citrullination status and biology of PPAD in P gingivalis and to characterise the anti-PPAD antibody response in RA and associated periodontal disease (PD). Methods: PPAD in P gingivalis cells and culture supernatant were analysed by immunoblotting and mass spectrometry to detect citrullination. Recombinant PPAD (rPPAD), inactive mutant PPAD (rPPAD C351S ), and N-terminal truncated PPAD (rPPAD Ntx ) were cloned and expressed in Escherichia coli . Patients with RA and healthy controls were assayed for IgG antibodies to citrullinated rPPAD and unmodified rPPAD C351S by ELISA. Anti-PPAD antibodies were correlated with anti-cyclic citrullinated peptide (third-generation) antibody levels, RA disease activity and PD status. Results: PPAD from P gingivalis is truncated at the N-terminal and C-terminal domains and not citrullinated. Only when artificially expressed in E coli, full-length rPPAD, but not truncated (fully active) rPPAD Ntx, is autocitrullinated. Anti-PPAD antibodies show no heightened reactivity to citrullinated rPPAD, but are exclusively directed against the unmodified enzyme. Antibodies against PPAD do not correlate with anti-cyclic citrullinated peptide levels and disease activity in RA. By contrast, anti-PPAD antibody levels are significantly decreased in RA patients with PD. Conclusions: PPAD autocitrullination is not the underlying mechanism linking PD and RA. N-terminal processing protects PPAD from autocitrullination and enhances enzyme activity. Anti-PPAD antibodies may have a protective role for the development of PD in patients with RA.